PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA MELALUI PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI DI PT. PEGADAIAN CABANG PROBOLINGGO - Putra, Achmad Bayu Perdana; Prasetyo, Indra (MAP (Jurnal Manajemen dan Administrasi Publik), 2024)
This research was conducted at PT Pegadaian Probolinggo Branch, this research aims to find out the influence of Work Motivation and Work Discipline through Career Development on Employee Performance at PT Pegadaian Probolinggo Branch, this research is explanatory research with a quantitative approach. The sample in this research was 54 employees at PT Pegadaian Probolinggo Branch. The sampling technique is saturated sampling (census), which is a sampling technique when all members of the population are used as samples. The data analysis technique uses PLS (Partial Least Square). The results of this research state that Work motivation has a significant and positive effect on employee performance. Work discipline has a significant and positive effect on employee performance. Work motivation has a significant and positive effect on career development. Work discipline has a significant and positive effect on career development. Career development has a significant and positive effect on employee performance. Work motivation has an indirect and significant effect on employee performance through career development. Work discipline has an indirect and significant effect on employee performance through career development.